JURIDICAL ANALYSIS AGAINST THE DISMISSAL POSITION OF CHAIRMAN THE CONSTITUTIONAL BASED ON THE RULING OF HONORARY COUNCIL OF THE CONSTITUTIONAL COURT NUMBER: 2/MKMK/L/11/2023: Constitutional Court - Putra, Irwan Sapta (Jurnal Pilar Keadilan, 2024)
This article examines the decision made by the honorary panel of the Constitutional Court regarding reports of violations of the code of ethics for constitutional judges made by Deni Inriyani against the chairman of the Constitutional Court, Anur Usman, who is the brother-in-law of the President of the Republic of Indonesia, namely Mr. Jokowi. Previously, the chairman of the Constitutional Court issued Decision Number 90/PUU-XXI/2023, the contents of which stated Article 169 letter q of Law Number 7 of 2017 concerning General Elections (State Gazette of the Republic of Indonesia of 2017 Number 182, Supplement to State Gazette of the Republic of Indonesia Number 6109 ) which states, "at least 40 (forty) years of age" is contrary to the 1945 Constitution of the Republic of Indonesia and has no binding legal force, as long as it is not interpreted as "at least 40 (forty) years of age or has/is occupy positions elected through general elections, including regional head elections." This research is a normative legal research with a case approach carried out from 2023 to 2024. From the results of this research it is known that the chairman of the Indonesian Constitutional Court was declared to have violated the judge's code of ethics and was removed as chairman of the Constitutional Court and was prohibited from examining disputes over the election of the President and Deputy President. in 2024.